Lineamientos de un modelo de enseñanza del idioma inglés en la modalidad E-Learning para los estudiantes de postgrado, talleres 1 y 2, de la Universidad Nacional de Loja - Peñaranda Requelme, Rocío Esperanza (2011)
This research work is on a study of Guidelines on a pattern English Teaching Learning Process by e-learning for postgraduate students, workshops 1 and 2 of Universidad Nacional de Loja. The objectives of this investigation work were: to analyze the actual course of English language for postgraduate students, to determine if the time of the course is enough for developing the skills of a foreign language and to determine the alternative guidelines based on a specific pattern by e-learning for postgraduate students of Educación a Distancia, Psicología Infantil, and Docencia y Evaluación Educativa de la Universidad Nacional de Loja. The applied methodology in the present research work was mainly participative because I got all the persons included in this research work, know the relevance of the work and the importance of their information in order to get the real results for benefit of this institution. The scientific method let me get the real knowledge through reliable instruments; and deductive method was a reference on the registered problems in the Language Institute to realize the problems. Through the inductive method it was established the pattern of teaching-learning by e-learning for postgraduate students of Educación a Distancia, Psicología Infantil, and Docencia y Evaluación Educativa, of Area de la Educación, el Arte y la Comunicación de la Universidad Nacional de Loja; the descriptive and statistic methods helped me to know the environment of the investigation and then organize the information, make the tables and graphics to know the corresponding analyses ad interpretations. Between the main results it was found that the Language Institute doesn´t have an specific pattern of teaching learning of English language for postgraduate students of Educación a Distancia, Psicología Infantil, and Docencia y Evaluación Educativa of the Area de la Educación, el Arte y la Comunicación of Universidad Nacional de Loja; that the authorities of this university represented by Rector, Coordinator of Language Institute, Head of PROMADIS of Area de la Educación, el Arte y la Comunicación all of them have the better disposition to help to introduce this pattern; the manner of the course that students receive is not according to the needs of this students because they are at a distance students, the contents of the course are not according to their requirements, they have problems with the tasks and these students have knowledge in handling computer instruments and in the use of NTICS. All these results helped me to get the conclusions with logical baselines in order to suggest the introduction of a new way English language teaching learning with a pattern of e-learning according to the students of Educación a Distancia, Psicología Infantil, and Docencia y Evaluación Educativa of the Area de la Educación, el Arte y la Comunicación de la Universidad Nacional de Loja. Finally I conclude that the introduction of a pattern of e-learning for English language teaching learning will get a better prestige for Universidad Nacional de Loja.